Hubungan antara status sosial ekonomi dengan kejadian stunting pada balita - da Gomez, Avelina Maria Rosari; Malonda, Nancy Swanida Henriette; Sanggelorang, Yulianty (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Indonesia faces significant nutritional challenges, namely high rates of stunting among toddlers. Stunting can begin during fetal development and continue after birth, but it usually becomes apparent at the age of two. The main causes of stunting are chronic malnutrition and recurrent infections experienced during the first 1,000 days of life. One of the underlying factors contributing to stunting is socioeconomic status. Purpose: To investigate the relationship between socioeconomic status and the incidence of stunting in infants. Method: A quantitative approach with an analytical observational design and a cross-sectional approach. The study population consists of infants aged 24–59 months in the Pineleng Health Center service area, with a sample size of 100. Sampling was conducted using probability sampling with simple random sampling. The instruments used include questionnaires and anthropometric measurements based on height-for-age (HAZ) indices. Data analysis was performed using the chi-square test and Fisher’s exact test. Results: There is a significant association between the father’s education (p = 0.002), the mother’s education (p = 0.002), and the mother’s occupation (p = 0.040) with stunting in toddlers in the Pineleng Health Center’s service area. Conversely, no association was found between the father's occupation (p = 1.000) and food and non-food expenditures (p = 1.000) with stunting in toddlers in the area. Conclusion: There is a significant relationship between socioeconomic status (parents' education, mother's occupation) and the incidence of stunting in toddlers in the working area of the Pineleng Community Health Center in Minahasa Regency. Suggestion: Parents should be more active in seeking information about meeting their children's nutritional needs through posyandu activities and nutritional counseling, and play a role in managing family resources to meet balanced food and nutritional needs. Keywords: Sosio-economic Status; Stunting; Toddlers. Pendahuluan: Indonesia menghadapi tantangan gizi yang signifikan yaitu tingginya angka stunting pada balita. Stunting dapat dimulai selama perkembangan janin dan berlanjut setelah kelahiran, tetapi biasanya menjadi terlihat pada usia dua tahun. Penyebab utama stunting adalah malnutrisi kronis dan infeksi berulang yang dialami selama 1.000 hari pertama kehidupan. Salah satu faktor yang mendasari terjadinya masalah stunting adalah status sosial ekonomi. Tujuan: Untuk menginvestigasi hubungan antara status sosial ekonomi dan kejadian stunting pada balita. Metode: Pendekatan kuantitatif dengan desain observasional analitik dan pendekatan cross sectional. Populasi dalam penelitian ini terdiri dari balita berusia 24-59 bulan di wilayah kerja Puskesmas Pineleng, dengan jumlah sampel sebanyak 100. Teknik pengambilan sampel dilakukan melalui probability sampling dengan metode simple random sampling. Instrumen yang digunakan mencakup kuesioner dan pengukuran antropometri berdasarkan indeks tinggi badan menurut umur (TB/U). Analisis data dilakukan menggunakan uji statistik chi-square dan fisher’s exact test. Hasil: Menunjukkan adanya hubungan signifikan antara pendidikan ayah (p = 0,002), pendidikan ibu (p = 0,002), dan pekerjaan ibu (p = 0,040) dengan kejadian stunting pada balita di wilayah kerja Puskesmas Pineleng. Sebaliknya, tidak ditemukan hubungan antara pekerjaan ayah (p = 1,000) serta pengeluaran pangan dan non-pangan (p = 1,000) dengan kejadian stunting pada balita di wilayah tersebut. Simpulan: Terdapat hubungan yang signifikan antara status sosial ekonomi (pendidikan orang tua, pekerjaan ibu) dengan kejadian stunting pada balita. Saran: Orang tua supaya lebih aktif mencari informasi tentang memenuhi kebutuhan gizi anak melalui kegiatan posyandu dan konseling gizi, serta berperan dalam mengelola sumber daya keluarga untuk memenuhi kebutuhan makanan dan gizi yang seimbang. Kata Kunci: Balita; Status Sosial Ekonomi; Stunting.